Biology and behavior of white stem borer (Scirpophaga fusciflua) on rice (Oryza sativa) in India - KUMAR, ANKIT; RAM, LAKHI; SINGH, RAM; SINGH, BANVIR (The Indian Journal of Agricultural Sciences, 2018)
The laboratory and screen house experiment was conducted to study the biology and behavior of Scirpophaga fusciflua Hampson (Lepidoptera: Crambidae) during kharif 2015. The female moth oviposited both on dorsal and ventral surfaces of the leaf. The eggs were laid in masses and covered with brownish hairs of anal tuft. The eggs were hatched in 5-7 days with an average of 5.25±0.09 days. The maximum eggs hatched on 5th day (93.62%) with 92.31% egg hatchability. The females laid eggs in the night between 9:00 pm to 11:00 pm during the study. The insect has five larval instars. The pupal period lasted for 7-9 days and the adults emerged out from the pupae at night between 6:00 pm to 8:00 pm during dusk hours. Adults exhibited sexual dimorphism. The number of eggs per female ranged from 64-212 with an average of 138.60±15.67 eggs. The longevity of male and female ranged from 2-3 days in male and 2-4 days in female, respectively. The morphometrics of different development stages are also discussed. This study is the first to describe the biology S. fusciflua in India.